Groundwater Quality Analysis In Sidomulyo Hamlet, Argomulyo Village, Kalaena District East Luwu County - Andri Widianto; Jamal Rauf Husain; Firman Nullah Yusuf (CV Insight Publisher, 2023)
The geographical condition of Kalaena District is one of the sub-districts in East Luwu Regency. Kalaena District is located at 2o 03' 00” – 2o 30' 31” South Latitude and 120 o 49’30” - 121 o 00’ 30” East Longitude with an area of 64.54 km2. Groundwater is part of the water that is below the surface of the ground, groundwater is a necessary need for the community, making the quality of groundwater very necessary to be maintained and maintained. The data collection stage is the activity of retrieving all the required field data. The data used in this study were obtained from the results of direct surveys in the field on several wells in Argomulyo village, taking water samples and then testing the pH value, color, taste, smell, turbidity, weather, well depth, water level, well diameter, citizen interview data and research documentation photos, then several samples were subjected to laboratory tests to find out the chemical content in the residents' wells. It is known that the results of the study show that the contents of TDS, DO, calcium, iron and chloride are still below the threshold, only turbidity has a value above the permitted threshold, the feasibility of shallow groundwater is based on Government Regulation of the Republic of Indonesia No.22 article 1 paragraph 37 of 2021 in the research area based on the results of chemical analysis and physical tests performed. fall into class 3 category.